2010
DOI: 10.1016/j.jvs.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Emergency endovascular treatment of early spontaneous nonaneurysmal popliteal artery rupture in a patient with Salmonella bacteremia

Abstract: Rupture of a nonaneurysmal popliteal artery and subsequent pseudoaneurysm formation is an exceedingly rare event after bacteremia caused by Salmonella spp. Only a few cases have been reported in the literature. Moreover, spontaneous popliteal artery rupture resulting from this pathology, to our knowledge, has not been reported. We describe an early spontaneous rupture of the popliteal artery complicated by acute compartment syndrome in a 67-year-old man who had recently experienced fever, chills, and diarrheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The cases reported in the literature are summarized in Supplementary Table S1 (refs. 22 56 ). The clinical features of the 4 cases treated at our hospital and the 53 cases reported in the literature are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The cases reported in the literature are summarized in Supplementary Table S1 (refs. 22 56 ). The clinical features of the 4 cases treated at our hospital and the 53 cases reported in the literature are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The commonest locations of non-typhoidal Salmonella mycotic aneurysms in the elderly include the abdominal aorta, followed by the thoracic aorta and then the iliofemoral artery [4] . Popliteal artery mycotic aneurysms secondary to non-typhoidal Salmonella (S. enteritidis being the most commonly implicated serovar) have been rarely reported in case reports, presenting predominantly with fever and leg swelling [5] , as with our patient.…”
Section: Discussionmentioning
confidence: 80%
“…Riga et al described five high-risk patients with peripheral infected aneurysms who were successfully treated by endovascular stenting [6] . Trellopoulos et al reported the first case of a patient with S. enteritidis bacteraemia, who had spontaneous rupture of the popliteal artery and was successfully treated by endovascular repair with a covered stent [5] . To the best of our knowledge, our patient is the second reported case.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiogram revealed absent valve vegetation with no significant valve dysfunction. The possibility of Salmonella endarterial infection was ruled out by negative blood cultures, and the absence of an antecedent clinical picture suggestive of bacteremia [ 6 ]. One etiology that has been described as a cause of pseudoaneurysms is connective tissue disorders [ 4 ].…”
Section: Discussionmentioning
confidence: 99%